Validation of the General Medication Adherence Scale in Saudi Patients With Chronic Diseases - Naqvi, Atta Abbas; AlShayban, Dhafer Mahdi; Ghori, Syed Azizullah; Mahmoud, Mansour Adam; Haseeb, Abdul; Faidah, Hani Saleh; Hassali, Mohamed Azmi (Frontiers in Pharmacology, 2019)
Objective The aim was to validate the General Medication Adherence Scale (GMAS) (English version) in Saudi patients with chronic disease. Methods A month long study was conducted in out-patient department of tertiary care hospitals in three cities of Saudi Arabia that collected data from a randomized sample of Saudi patients with chronic disease. The study aimed to achieve an item-to-subject ratio greater than 1:10. Factor analyses were conducted and fit indices were calculated. Convergent, discriminant, known group and concurrent validities were analysed. Internal consistency was determined using test-retest reliability using Cronbach’s alpha (α), McDonald’s coefficient omega (ωt) and Pearson’s correlation coefficient (ρ). Sensitivity analysis was conducted. Data was analysed through SPSS version 23. The study was ethically approved, i.e., (IRB-129-26/6/1439). Results The survey gathered responses from 171 patients with a response rate of 85.5%. An item-to-subject ratio of 1:15 was achieved. Factor analysis revealed a three-factor structure with acceptable fit indices, i.e., NFI = 0.93, TLI = 0.99 and CFI = 0.99, i.e., greater than 0.9. The value of RMSEA was 0.01, i.e., less than 0.08. The tool established construct validity, i.e., convergent and discriminant validities. Known group and concurrent validities were also established. An α value of 0.74 and ωt value of 0.92 was reported. Test-retest reliability ρ = 0.82, p<0.001. The tool had high sensitivity (>75%) and specificity (>80%). Conclusion The GMAS-English was successfully validated in Saudi patients with chronic disease. Keywords Medication adherence; patient compliance; medication persistence; chronic illness; Saudi Arabia